2016
DOI: 10.1007/s40211-016-0170-5
|View full text |Cite
|
Sign up to set email alerts
|

Ärztlicher Personalbedarf in der Versorgungspsychiatrie – eine „Bottom-Up“ Personalbedarfsberechnung am Beispiel der Psychiatrischen Abteilung des Donauspitals in Wien

Abstract: Severely ill psychiatric patients seem to be undertreated because of low staffing of psychiatric departments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
2
0
1
Order By: Relevance
“…Regarding mental health care or psychosocial care, the main barriers mentioned in the literature range from stigmatisation, information deficits, and waiting times among people with mental health problems (cf. [27]) to barriers to accessing psychotherapy as well as psychiatric inpatient care and psychiatric care in hospital outpatient departments [20,[27][28][29][30][31][32][33][34][35][36]. Previous studies have identified financial barriers to accessing psychotherapy, often in combination with other barriers such as long-term unemployment, risk of social exclusion, or language barriers [29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding mental health care or psychosocial care, the main barriers mentioned in the literature range from stigmatisation, information deficits, and waiting times among people with mental health problems (cf. [27]) to barriers to accessing psychotherapy as well as psychiatric inpatient care and psychiatric care in hospital outpatient departments [20,[27][28][29][30][31][32][33][34][35][36]. Previous studies have identified financial barriers to accessing psychotherapy, often in combination with other barriers such as long-term unemployment, risk of social exclusion, or language barriers [29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding mental health care or psychosocial care, the main barriers mentioned in the literature range from stigmatisation, information de cits, and waiting times among people with mental health problems (cf. [26]) to barriers to accessing psychotherapy as well as psychiatric inpatient care and psychiatric care in hospital outpatient departments [19,[26][27][28][29][30][31][32][33][34][35]. Previous studies have identi ed nancial barriers to accessing psychotherapy, often in combination with other barriers such as long-term unemployment, risk of social exclusion, or language barriers [28][29][30][31].…”
Section: Barriers For People With Chronic Conditions In Austriamentioning
confidence: 99%
“…Dass die Personalausstattung in Deutschland nach den gesetzlichen Vorgaben angesichts vielfältig gestiegener Aufgaben vor allem in der Dokumentation und kontinuierlich gestiegener Aufnahmezahlen grenzwertig knapp ist und zu impliziten Rationierungen führt, ist gut bekannt [19]. Gerade in der Psychiatrie bedürfte eine qualitativ hochwertige und nach humanen Gesichtspunkten geführte Patientenarbeit einer personellen Ausstattung, von der wir sowohl in Deutschland wie auch in Österreich weit entfernt sind [20]. Einen einfachen linearen Zusammenhang zwischen der Personalausstattung in der Pflege und der Öffnung psychiatrischer Stationen zu postulieren, greift freilich sicher zu kurz [16].…”
Section: Diskussionunclassified